Nuclear Mechanosensation and Mechanotransduction in Vascular Cells - Salvador, Jocelynda; Iruela-Arispe, M. Luisa (Frontiers in Cell and Developmental Biology, 2022)
Vascular cells are constantly subjected to physical forces associated with the rhythmic activities of the heart, which combined with the individual geometry of vessels further imposes oscillatory, turbulent, or laminar shear stresses on vascular cells. These hemodynamic forces play an important role in regulating the transcriptional program and phenotype of endothelial and smooth muscle cells in different regions of the vascular tree. Within the aorta, the lesser curvature of the arch is characterized by disturbed, oscillatory flow. There, endothelial cells become activated, adopting pro-inflammatory and athero-prone phenotypes. This contrasts the descending aorta where flow is laminar and endothelial cells maintain a quiescent and atheroprotective phenotype. While still unclear, the specific mechanisms involved in mechanosensing flow patterns and their molecular mechanotransduction directly impact the nucleus with consequences to transcriptional and epigenetic states. The linker of nucleoskeleton and cytoskeleton (LINC) protein complex transmits both internal and external forces, including shear stress, through the cytoskeleton to the nucleus. These forces can ultimately lead to changes in nuclear integrity, chromatin organization, and gene expression that significantly impact the organism such as the high incidence of atherosclerosis in progeria. Therefore, there is strong motivation to understand how endothelial nuclei can sense and respond to physical signals and how abnormal responses to mechanical cues can lead to disease. Here, we review the evidence for a critical role of the nucleus as a mechanosensor and the importance of maintaining nuclear integrity in response to continuous biophysical forces, specifically shear stress, for proper vascular function and stability.